Arabic Language Program Management at Al-Hidayah Islamic Boarding School, Batu City - Utomo, Dimas Wahyu; Aminudin, Aminudin; Maksum, M. Syukron; Hasanah, Nur (Journal of Educational Management Research, 2025)
This study aims to describe the management of the Arabic language learning program at the Al-Hidayah Batu Islamic Boarding School, which includes aspects of planning, organization, implementation, and evaluation. This study uses a qualitative approach with field research. Data were collected through observation, in-depth interviews with the program head and Arabic language teachers, and documentation of learning activities. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that the program planning is carried out systematically by the asatidz council through the preparation of a pesantren-based curriculum with the Takhotub and Al-Muhawaroh books as the main sources. Organization is carried out by implementing a line and staff structure to clarify the division of tasks and responsibilities among members. Learning is carried out every morning after the dawn prayer using various methods such as the mubasyarah thariqah and ta'bir thariqah, which emphasize the active involvement of students. Evaluation is carried out periodically through oral and written exams and follow-up assessments to improve the quality of learning. The research findings are expected to be a reference for other Islamic boarding schools in developing an adaptive, professional, and sustainable Arabic language program management model.